Virulent Factor‐Targeted Point‐of‐Care Biosensor for Detection of Staphylococcus Aureus Infections - Zahra Marvi; Yara Raphael; Dario Job; Graziele Cruzado; Geraldine Merle (Advanced Sensor Research)
Abstract Rapid detection of pathogenic bacteria like Staphylococcus aureus (S. aureus) is crucial for timely diagnosis and infection control. Aureolysin (Aur), an extracellular metalloprotease involved in S. aureus pathogenesis, is a promising biomarker. This study presents a rapid, low‐cost, label‐free electrochemical immunosensor for aureolysin detection using antibody‐gold (Ab‐Au) bioconjugates. Anti‐aureolysin antibodies are immobilized on gold nanospikes via 1‐Ethyl‐3‐(3‐dimethylaminopropyl)carbodiimide / N‐Hydroxysuccinimide (EDC/NHS) chemistry and screen‐printed gold electrodes (SPGEs). The detection relied on changes in peak current from antigen‐antibody complex formation, measured through differential pulse voltammetry (DPV). Selectivity tests confirmed the sensor's specificity for S. aureus, with no cross‐reactivity against Escherichia coli or Pseudomonas aeruginosa. A strong linear correlation (R2 = 0.9739) between peak current and logarithmic S. aureus concentrations is observed, with a detection limit of 5 pg·mL⁻¹ in buffer and 2 Colony‐forming unit (CFU) mL⁻¹ in bacterial cultures. The sensor also detected S. aureus in biofilms, highlighting its potential for real‐world use. Offering rapid detection within 1h, high sensitivity, and specificity, this immunosensor is a promising point‐of‐care tool for S. aureus detection in clinical settings. This approach greatly enhances the sensor's effectiveness in real‐world clinical applications, where biofilm formation often complicates diagnosis and treatment.